Ø§Ù„Ø§ØØªØ¬Ø§Ø¬ Ø¨Ø§Ù„Ù‚Ø¯Ø± ÙÙŠ Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ… - Fouly, Nabil (IAIN Surakarta, 2019)
This paper revolves around those verses ofÂ Quranin whichÂ Quranstates the argument of the non-believers provide for the justification of their disbelief and acts of polytheism and that is the argument ofÂ Qadar.The argument follows that the non-believers are not to be blamed for their disbelieve because these acts are been decreed by God for them. The paper emphasises upon a detail analysis of their argument and upon theÂ quranicÂ response to them by exposing their flawed argumentation and wrong claim. The paper then studies and establishes the position of belief inÂ qadarÂ and itâ€™s position and place within the Islamic belief system, and furthermore studies those different issues which are discussed and dealt within thoseÂ Quranicverses related toÂ qadar.Moreover the interpretations of thoseÂ Quranicverses which states this claim of non-believers according to differentÂ Mufassirinare studied and analysed and then in the end a generalÂ QuranicÂ view regarding howÂ Qurandeals with the issue of â€œargumentation based upon the concept ofÂ Qadarâ€is presented in the paper